The Use of Languages by Valencian Business-to-Consumer Service Companies in their Telematic Communications - Català-Oltra, Lluis; Penalva-Verdù, Clemente (HERMES - Journal of Language and Communication in Business, 2021)
This study analyses the languages used by companies in their telematic means (website, social media, etc.) in a specific geographical area, the Valencian Community (Spain), where two official languages (Catalan and Spanish) coexist and where there is a large influx of foreign tourists (mainly British). More specifically, the aim of the study is to understand the weight each language has in companies’ telematic communication. The theoretical approach used for the analysis is the centre-periphery model, which is used to analyse national identity and language. Different techniques (use of secondary sources, mystery shopping, content analysis and direct observation) have been used in the quantitative empirical study to obtain a statistically disaggregated data matrix. The results strongly emphasize the peripheral and marginal position of Catalan in this region, and, on an international scale, the resistance of Spanish, which clearly maintains its hegemonic position over English in the telematic communications of these companies.